RATIO LEGIS FOR THE ABOLITION OF GIRIK AS EVIDENCE OF LAND OWNERSHIP UNDER GOVERNMENT REGULATION NUMBER 18 OF 2021 - Putri, Eka Ratna; Rahayu, Mella Ismelina Farma (Awang Long Law Review, 2025)
Land holds a crucial role in the lives of Indonesian people, serving not only as an economic asset but also as a social and cultural symbol. However, land ownership based on girik documents often leads to disputes due to the uncertainty of its legal status. This study aims to analyze the ratio legis behind the abolition of girik as evidence of land ownership based on Article 96 of Government Regulation Number 18 of 2021, which mandates the conversion of all customary lands into certificates no later than 2026. The research method employed is normative juridical, using statutory and conceptual approaches. The data sources include primary, secondary, and tertiary legal materials analyzed qualitatively. The results show that the abolition of girik is grounded in the principles of legal certainty, administrative justice, and the need to establish an orderly and integrated national land administration system. This policy is a logical consequence of the transition of Indonesia’s land law system toward a single system based on certificates as the only valid proof of ownership. The abolition of girik is expected to prevent agrarian disputes, reduce opportunities for land-related fraud, and promote a fair and modernized land administration system that ensures legal certainty.